Additively Manufactured Polyetheretherketone (PEEK) with Carbon Nanostructure Reinforcement for Biomedical Structural Applications. Issue 10 (23rd July 2020) - Alam, Fahad; Varadarajan, Kartik M.; Koo, Joseph H.; Wardle, Brian L.; Kumar, Shanmugam
Abstract : This study is focused on carbon nanostructures (CNS), including both carbon nanotubes (CNTs) and graphene nanoplatelets (GNPs), reinforcement of medical‐grade polyetheretherketone (PEEK), and in vitro bioactivity for biomedical structural applications. CNS/PEEK scaffolds and bulk specimens, realized via fused filament fabrication (FFF) additive manufacturing, are assessed primarily in the low‐strain linear‐elastic regime. 3D printed PEEK nanocomposites are found to have enhanced mechanical properties in all cases while maintaining the desired degree of crystallinity in the range of 30–33%. A synergetic effect of the CNS and sulfonation toward bioactivity is observed—apatite growth in simulated body fluid increases by 57% and 77%, for CNT and GNP reinforcement, respectively, doubling the effect of sulfonation and exhibiting a fully‐grown mushroom‐like apatite morphology. Further, CNT‐ and GNP‐reinforced sulfonated PEEK recovers much of the mechanical losses in modulus and strength due to sulfonation, in one case (GNP reinforcement) increasing the yield and ultimate strengths beyond the (non‐sulfonated) printed PEEK. Additive manufacturing of PEEK with CNS reinforcement demonstrated here opens up many design opportunities for structural and biomedical applications, including personalized bioactivated surfaces for bone scaffolds, with further potential arising from the electrically conductive nanoengineered PEEK material toward smart and multifunctional structures. Abstract : Carbon nanostructures (CNS) are incorporated into polyetheretherketone (PEEK) feedstock for additive manufacturing of biomedical structural implants. CNS are found to positively affect the structural performance, while the observed synergy between the CNS and sulfonation enhances the bioactivity of 3D printed PEEK nanocomposite implants.